2011
DOI: 10.1371/journal.pcbi.1002022
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Magnetic Stimulation of Central Nervous System Neurons

Abstract: Transcranial magnetic stimulation (TMS) is a stimulation method in which a magnetic coil generates a magnetic field in an area of interest in the brain. This magnetic field induces an electric field that modulates neuronal activity. The spatial distribution of the induced electric field is determined by the geometry and location of the coil relative to the brain. Although TMS has been used for several decades, the biophysical basis underlying the stimulation of neurons in the central nervous system (CNS) is st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
151
3
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(170 citation statements)
references
References 58 publications
12
151
3
4
Order By: Relevance
“…Although there are widespread applications of electromagnetic stimulation in cognitive research and disease treatment, many questions still remain about the mechanisms underlying the neuromodulation by electromagnetic fields (Wagner et al 2007;Peterchev et al 2012). It has been shown that the basic principle for these noninvasive techniques is that they induce an extracellular electric field around the brain tissue of interest to modulate corresponding neuronal activity and behavior (Peterchev et al 2012;Pashut et al 2011). Therefore, exploration of the neuromodulatory mechanism of electromagnetic fields requires knowledge of how an induced extracellular electric field interacts with and modifies neuronal dynamics (Peterchev et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are widespread applications of electromagnetic stimulation in cognitive research and disease treatment, many questions still remain about the mechanisms underlying the neuromodulation by electromagnetic fields (Wagner et al 2007;Peterchev et al 2012). It has been shown that the basic principle for these noninvasive techniques is that they induce an extracellular electric field around the brain tissue of interest to modulate corresponding neuronal activity and behavior (Peterchev et al 2012;Pashut et al 2011). Therefore, exploration of the neuromodulatory mechanism of electromagnetic fields requires knowledge of how an induced extracellular electric field interacts with and modifies neuronal dynamics (Peterchev et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Since these criteria depend on the geometry of stimulators, most researchers do not introduce the best stimulator, but the results can be helpful in future designs [5][6][7][8][9]. Obtaining the thresholds of excitability, which depends on the stimulator parameters, is common in the literature [4,[10][11][12][13][14][15]. In all of these pieces of research, diagrams such as excitability thresholds and parameter impact are determined to help the design of stimulators and cognition of excitable cells.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical evidences point out that magnetic field can induce an electrical field that modulates neuronal activity of special brain tissue (Legros et al 2010;Cook et al 2004). For example, transcranial magnetic stimulation (TMS) can disrupt or induce activity in a particular brain tissue (Pashut et al 2011;Kamitani 2011). It provides a valuable tool to map brain function, such as motor and sensory processes, attention, memory, language, and neuronal plasticity (Di Lazzaro et al 2004;Lisanby et al 2000;Terao and Ugawa 2002;Ziemann and Rothwell 2000).…”
Section: Introductionmentioning
confidence: 99%